Descending endograft for DeBakey type 1 aortic dissection: pro - Berretta, Paolo (Ann Cardiothorac Surg, 2016)
The surgical management of patients with DeBakey type 1 acute aortic dissection (DBT1-AAD) represents a major challenge for aortic surgeons. It has been demonstrated that the distal false lumen remains patent in about 70% to 80% of patients undergoing DBT1-AAD surgery and that a patent false lumen worsens the prognosis. In order to improve long term outcomes and reduce the frequency of late aneurysm formation and reoperation, a more aggressive primary operation involving total arch replacement (TAR) and concomitant antegrade stenting of the descending thoracic aorta (DTA) with a frozen elephant trunk (FET) has been introduced. Such extensive operations, however, remain controversial due to their increased technical complexity and perceived higher operative mortality and morbidity. This perspective article will overview the rationale behind, and the potential advantages and current evidence for, FET surgery in acute aortic dissection.